The confrontation between nature and culture in the novel " Night post" by Hoda Barakat based on the theory of cultural semiotics - Nouidi, Abdelouahid; Maasoumi, Mahrane (Journal of Human Sciences, 2023)
Semiotics as a branch of research methods, extracts hidden meanings in the texts in which the author hid his thoughts and opinions, and nature is a stable model of society that was far from the changes made by man, and on the contrary, there is a culture made that was not far from human intervention. The Lebanese writer Hoda Barakat, in order to fight colonialism and to refer to the most important events of the present era, wrote "The Night Post" in which she criticized foreigners and the displacement of Arabs. This research seeks to extract the social elements of Russian in the light of cultural semiotics, in order to analyze the patterns of nature and culture, and to reveal how these two models affect each other in the reflection of the current conditions of society, and the diversity of signs indicates the depth of the author's vision of the social idea, the reflection of issues, and the relationship between The various phenomena in order to educate the Arabs.